Women's Status and Violence against Young Married Women in Rural Nepal - Tamang Jyotsna; Puri Mahesh; Lamichhane Prabhat; Dulal Bishnu (BMC, 2011)
Abstract Background Studies conducted around the world consistently show the existence of violence against women. Despite the increasing number of studies being conducted on violence against young married women elsewhere, this subject has received little attention from researchers and policy makers in Nepal. This paper assesses the prevalence of violence among young married women in rural Nepal. Specifically, it examines [factors related to] women's status in order to better understand the risk of violence. Methods A cross-sectional study was conducted in 2009 among 1,296 young married women aged 15-24 years in four major ethnic groups. Bivariate analysis and multivariate logistic regression were used to examine the association between selected risk factors and violence. Results More than half the women (51.9%) reported having experienced some form of violence in their lifetime. One-fourth (25.3%) reported physical violence and nearly half (46.2%) reported sexual violence. Likewise, one-third (35.8%) of women reported experiencing some form of violence in the past 12 months. No or little inter-spousal communication and low autonomy of women significantly increases the odds of experiencing violence among married women. Conclusions The violence against women is quite common among young married women in rural Nepal. Although the Domestic Violence and Punishment Act 2066 has been enacted, equal attention needs to be given to increasing women's autonomy and activities that encourage inter-spousal communication. Furthermore, more research is required in Nepal that examines dynamics of violence perpetrated by husbands.